Development of Telecounseling Media Based on Facial Expression Analysis as A Tool for Detecting Suicide Tendencies in Students - Amiirah Aniisah; Aditya Ramadito Rahman; M. Aldwin Priyatama; Wzamah Al Hussein; Muhibbudin Fadhli; Eka Pramono Adi; Deka Dyah Utami (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2024)
This research is motivated by a 20% increase in suicide cases among college students in Malang City. It aims to develop a telecounseling platform based on Facial Expression Analysis (FEA) to detect suicidal tendencies. The development follows a Research and Development (R&D) methodology, adapted from the ADDIE model and modified into four stages: analysis, design, development, and evaluation. Needs analysis shows that both counselors and clients require features such as scheduling, FEA reports, bibliocounseling, and forums. Expert validation results indicate that this platform is highly relevant, user-friendly, and engaging, with a validity index of 1. The final evaluation shows that the platform can enhance counselors' effectiveness and assist clients in managing their emotional issues. The designed features support a more comprehensive and in-depth counseling process.